Kelincahan Bisnis dan Maqasid al-Syariah : Menyelaraskan Prinsip Etika dengan Dinamika Ekonomi - Ahmad Maulidizen (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The global economy is increasingly marked by volatility, uncertainty, and disruption, compelling organizations to adopt business agility as a means of survival and competitiveness. Conventional agility emphasizes speed, responsiveness, and innovation, yet often lacks the ethical foundation required for long-term sustainability. In contrast, Islamic economic thought, guided by Maqasid al-Shariah—the preservation of religion, life, intellect, lineage, and wealth—prioritizes justice, fairness, and social responsibility in economic activities. This study analyzes how the principles of Maqasid can be aligned with business agility to form an ethically grounded and adaptive business model. Employing a qualitative research design with a library research approach, the study synthesizes insights from existing literature on agility, Islamic economics, and Maqasid through thematic content analysis. The findings indicate that while agility strengthens resilience and competitiveness, it requires Maqasid as a moral compass to ensure value-driven adaptability. The integration of agility and Maqasid creates a synergy that enables Islamic enterprises not only to withstand global turbulence but also to differentiate themselves as ethical, sustainable, and competitive actors in the global market. This research therefore proposes a Shariah-compliant agility model that balances responsiveness with ethical accountability, offering theoretical contributions to academic discourse and practical implications for Islamic financial institutions, halal industries, and Shariah-based SMEs. The study also highlights the role of policymakers in developing supportive frameworks that foster innovation while safeguarding Shariah compliance. Overall, the study underscores that agility guided by Maqasid is not merely a survival strategy but a pathway to global leadership in ethical and sustainable business practices.